Raum für Raum : 7 Installationen. - Neue Galerie am Landesmuseum Joanneum, Graz (Graz : Neue Galerie am Landesmuseum Joanneum, 1989)
Anger, W.W. ; Gamauf, Susanne ; Gruppe Teer ; Kriesche, Richard ; Makra, Manfred ; Xaver, Franz ; Zinganel, Michael
Raum für Raum : 7 Installationen, Neue Galerie am Landesmuseum Joanneum, Graz, 23. Mai - 18. Juni 1989
boek